EVALUASI KINERJA REKSADANA SAHAM DI INDONESIA PERIODE APRIL-JULI 1997 - Deddy Marciano; Suad Husnan (Journal of Management and Business, 2002)
The prime focus of this paper is evaluation of Indonesian Mutual Funds, which are investing the funds on stock. Mutual fund is a portfolio, which managed by professional fund manager. The professional fund manager who always seek a new information connecting with their portfolio has a better information than individual investor. The mutual fund's portfolio should has higher performance than individual investor’s portfolio as well as the market's portfolio due to asymmetric information: The statistical results use mean difference t-test to support our hypothesis that the mutual fund's portfolio has a better performance than individual investor's portfolio as well as the market's portfolio.